Direct and indirect effects of servant and ethical leadership styles on employee creativity: mediating role of organizational citizenship behavior. Issue 1 (26th July 2022) - Hanaysha, Jalal Rajeh; Kumar, V.V. Ajith; In'airat, Mohammad; Paramaiah, Ch.
Abstract : Purpose: This research mainly aims to test the impact of two leadership styles (ethical and servant leadership) on employee creativity; and to determine whether organizational citizenship behavior (OCB) mediates the relationships between them. Design/methodology/approach: The paper relied on a quantitative research approach with a sample of 213 staff from public universities in the United Arab Emirates. In this paper, the partial least square approach (PLS-SEM) was employed in order to verify the proposed hypotheses. Findings: The outcomes confirmed that OCB has a positive impact on employee creativity. Additionally, the findings indicated that ethical leadership positively affected OCB and employee creativity. It was also confirmed that servant leadership has a significant positive impact on OCB and employee creativity. Finally, the findings revealed that OCB fully mediates the linkages among servant and ethical leadership and employee creativity. Originality/value: This paper acknowledges the existing gaps in the prior literature, and enables us to understand clearly about the significance of ethical as well as servant leadership in affecting employee creativity via OCB as a mediator.